2021
DOI: 10.35877/454ri.asci31109
|View full text |Cite
|
Sign up to set email alerts
|

Clustering method for spread pattern analysis of corona-virus (COVID-19) infection in Iran

Abstract: The COVID-19 is outbreak from China and infected more than 131,652 people and caused 7,300 deaths in Iran. Unfortunately, the infection numbers and deaths are still increasing rapidly which has put the world on the catastrophic abyss edge. Application of data mining to perform pattern recognition of infection is mainly used for preparing the spread mapping which considered in this work for spatiotemporal distribution assessment and spread pattern analysis of corona-virus (COVID-19) infection in Iran

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 5 publications
(4 reference statements)
0
17
0
Order By: Relevance
“…Made et al [34] applied geospatial visualization techniques to study the distribution of COVID-19 incidence rates in Bosnia and Herzegovina on a series of maps using ELIS (Epidemic Location Intelligence System). In another study by Chen et al [32], spatial distribution of COVID-19 incidence was shown on a map, while the rest of the analysis was largely based on statistical analysis.…”
Section: Resultsmentioning
confidence: 99%
“…Made et al [34] applied geospatial visualization techniques to study the distribution of COVID-19 incidence rates in Bosnia and Herzegovina on a series of maps using ELIS (Epidemic Location Intelligence System). In another study by Chen et al [32], spatial distribution of COVID-19 incidence was shown on a map, while the rest of the analysis was largely based on statistical analysis.…”
Section: Resultsmentioning
confidence: 99%
“…Spectral clustering [21][22] uses the top eigenvectors of a matrix derived from the input data and transforms the clustering problem into a graph cut problem. The graph cutting approach clusters data points by attribute such that densely packed points are in same cluster, whereas the sparse are in different clusters.…”
Section: Spectral Clustering (Sc)mentioning
confidence: 99%
“…Especially during the Covid-19 pandemic, clustering was also used to prevent epidemics. As in Iran, clustering incorporates geographic information systems (GIS) based on disease situations in different regions, which helps to identify diseasespreading trends and determines the possibility of the virus spreading [22].…”
Section: Applications Of Clustering In Some Areasmentioning
confidence: 99%